Implementation of Contextual Learning Strategies in Small Class Sunday Schools - Luciana Haryanto; Yusep Arimatea; Lasmauli Gurning; Napoleon Manalu (Riviera Publishing, 2024)
Effective learning strategies are very important in achieving learning objectives, especially in the context of Christian Religious Education in Sunday Schools. One of the strategies that can be applied is Contextual Teaching and Learning. This research aims to analyze the implementation of contextual learning strategies in small class Sunday School. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews, and document analysis. The participants consisted of Sunday School teachers and small class students. The results show that the implementation of contextual learning strategies in small class Sunday School includes seven main components: constructivism, discovery, questioning, learning community, modeling, reflection, and authentic assessment. This strategy is effective in improving students' understanding and engagement in the learning process. The implementation of contextual learning strategies in small class Sunday School is proven to facilitate meaningful learning that is relevant to students' daily lives. This strategy can be an alternative for teachers in designing and implementing Christian Religious Education learning that is more contextual and effective.